P06 Olesoxime improves specific features of the HD pathology. (29th August 2012) - Clemens, LE; Wlodkowski, TT; Eckmann, J; Eckert, S; Michaud, M; Yu, L; Portal, E; Bordet, T; Pruss, R; Eckert, GP; Riess, O; Nguyen, HP
Abstract : Background: Olesoxime, a cholesterol-oxime, is a neuroprotective compound initially developed for the treatment of ALS (Bordet et al 2007). It interacts with proteins on the outer membrane of mitochondria (OMM) and inhibits the opening of the mitochondrial permeability transition pore (mPTP). Furthermore, it was found to accelerate oligodendrocyte maturation, thereby enhancing myelination (Magalon et al 2012). Since both mitochondrial function and myelination are impaired in HD (Lin & Beal, 2006; Xiang et al 2010), we evaluated the effect of olesoxime on the behavioural and neuropathological phenotype of the BACHD rat. Methods: BACHD rats and their wild type littermates were fed ad libitum with either an olesoxime-containing or a control diet beginning at 5 weeks of age (n=15/group). Behavioural observations were carried out during a 12 months study period and neuropathology and mitochondrial function were investigated subsequently (n=4–6/group). Results: Olesoxime treatment improved the cognitive and psychiatric phenotype in BACHD rats, which might be associated with a reduced mhtt accumulation found in the prelimbic cortex that is involved in learning and emotionality. It further increased the width of axon bundles in the striatum, which was significantly decreased in BACHD rats compared to wild types, possibly due to an improved myelination. Olesoxime was further capable of restoring mitochondrial respiratory chain function, rescuing a deficit in the expression of OMM proteins and normalise mitochondrial membrane fluidity. Conclusions: Olesoxime did not improve motor and metabolic function but it ameliorated the cognitive, psychiatric and mitochondrial pathology in the BACHD rat.